2023
DOI: 10.3389/fimmu.2023.1188605
|View full text |Cite
|
Sign up to set email alerts
|

OVX033, a nucleocapsid-based vaccine candidate, provides broad-spectrum protection against SARS-CoV-2 variants in a hamster challenge model

Abstract: Spike-based COVID-19 vaccines induce potent neutralizing antibodies but their efficacy against SARS-CoV-2 variants decreases. OVX033 is a recombinant protein composed of the full-length nucleocapsid (N) protein of SARS-CoV-2 genetically fused to oligoDOM®, a self-assembling domain which improves antigen immunogenicity. OVX033 including N as an antigenic target is proposed as new vaccine candidate providing broad-spectrum protection against sarbecoviruses. OVX033 demonstrated its ability to trigger cross-reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…Indeed, robust titers of N-specific antibodies as well as sufficient levels of N-specific T cells were abundantly found in patients infected with SARS-CoV-2 [ 31 , 32 ]. This has also been confirmed in previous studies, when immunization with monovalent N-based vaccine candidates already showed the immunogenic and protective potential in preclinical studies [ 33 , 34 ]. The suitability of the N-protein has also been demonstrated using MVA as a vaccine vector platform.…”
Section: Introductionsupporting
confidence: 81%
See 1 more Smart Citation
“…Indeed, robust titers of N-specific antibodies as well as sufficient levels of N-specific T cells were abundantly found in patients infected with SARS-CoV-2 [ 31 , 32 ]. This has also been confirmed in previous studies, when immunization with monovalent N-based vaccine candidates already showed the immunogenic and protective potential in preclinical studies [ 33 , 34 ]. The suitability of the N-protein has also been demonstrated using MVA as a vaccine vector platform.…”
Section: Introductionsupporting
confidence: 81%
“…No N-specific CD8+ T cells were detected in control-vaccinated and MVA-ST- and MVA-ST/N-vaccinated mice. In previous studies, N-specific T cells have been hypothesized to induce a broader protective potential than S-specific T cells due to the higher conservation of the N-protein [ 34 ]. However, the impact of N-specific T cells for a more rapid protective capacity has not been evaluated in more detail.…”
Section: Discussionmentioning
confidence: 99%
“…Vaccination with this prototype led to the generation of non-neutralizing but specific antibodies involved in Fc-mediated cellular responses. In a hamster challenge model, the OVX033 injected with a cholesterol/squalene-based adjuvant provided cross protection against B.1, B.1.617.2 and B.1.1.529 SARS-CoV-2 VOCs, as manifested by reduced weight loss, impaired pulmonary replication of the virus, and reduced lung tissue damage [ 50 ].…”
Section: Development Of N-based Broadly Protective Vaccine Prototypesmentioning
confidence: 99%
“…The nucleocapsid proteins of many coronaviruses are highly immunogenic and expressed abundantly in infected cells, making them easy targets for antigen-specific T cells (Cong et al, 2020; Dutta et al, 2020; Hasanpourghadi et al, 2023). Other studies have reported the benefit of vaccination with the nucleocapsid protein of SARS-CoV-2, showing protective immunity in animal models receiving the nucleocapsid protein alone (Primard et al, 2023) or in combination with the spike protein (Chiuppesi et al, 2022; Hasanpourghadi et al, 2023). In our hamster study, we detected cellular immune responses against the spike protein, but not against the nucleocapsid protein.…”
Section: Discussionmentioning
confidence: 99%